Proses Penilaian Prestasi Kerja Pegawai Negeri Sipil Pada Kantor Unit Penyelenggara Bandar Udara - Moh. Agus Suhartono; Tehubijuluw Zacharias; Faizal Madya (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
The purpose of the study was to analyze the identification of the process in the SWOT strategy which was carried out in improving employee performance appraisal, at the Karel Sadsuitubun Airport Organizing Unit office. This research is qualitative research with a focused case study approach. Data was collected through in-depth open interviews, observation, and documentation. The data analysis technique is limited by using SWOT analysis (Strength, Weaknesses, Opportunities, and Threats Analysis) so that the structure and strategic level of these factors can be known. From the results of data presentation and data analysis, it can be concluded that the performance appraisal of officers at Karel Sadsuitubun Airport has referred to the applicable regulations and in terms of improving Leadership Competence in carrying out the assessment, it is carried out through training or workshops.Keywords: Evaluation, Process, Assessment, Task Achievement